THE INFLUENCE OF SOCIAL MEDIA MARKETING, PRODUCT QUALITY AND PRICES ON CONSUMER PURCHASING DECISIONS THROUGH CUSTOMER TRUST INTERVENING VARIABLES ON MSMES IN MAYANG DISTRICT, JEMBER REGENCY - Susbiyani , Arik; Supeni, Retno Endah; Adyasa, Jery Candra (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study explores the influence of social media marketing, product quality, and price on consumer purchasing decisions through the intervening variable of customer trust in MSMEs in Mayang District, Jember Regency. The main objective of this study is to understand the relationship between these variables and provide guidance for MSMEs actors in optimizing their marketing strategies. Method: This study uses a quantitative approach with a survey involving MSME consumers. Data were collected through questionnaires distributed using Google Form and analyzed using the Structural Equation Modeling (SEM) technique. Results: The results of the study indicate that social media marketing, product quality, and price have a significant influence on consumer purchasing decisions through customer trust. The implications of this study indicate that marketing strategies that focus on increasing customer trust can improve purchasing decisions and consumer loyalty. Novelty: This study makes an important contribution to the academic literature and offers practical guidance for MSMEs in developing more effective marketing strategies.